2017
DOI: 10.1007/s11999-017-5252-6
|View full text |Cite
|
Sign up to set email alerts
|

High Survivorship and Little Osteoarthritis at 10-year Followup in SCFE Patients Treated With a Modified Dunn Procedure

Abstract: Level IV, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 76 publications
1
51
0
5
Order By: Relevance
“…26 Ziebarth et al had no complications, 2 and at 12 years follow-up they found in 42 patients no AVN and an 9% overall complication rate, though secondary impingement deformi-ties remained in some patients, and secondary surgical procedures undergoing open procedures for impingement deformities (14%). 27 Huber et al 28 found 5 out of 28 patients (18%) with overall complications and 1 (3%) AVN; Madan et al 29 reported 5 out of 28 patients (18%) with overall complications and 4 (14%) AVN, Sankar et al 30 reported 41% with overall complications and 7 out of 27 patients (26%) AVN, and Upasani et al 7 reported 16 out of 43 patients (37%) with overall complications and 10 (23%) AVN. Except the Bernese group, the others had similar complication rates and this is carefully to be considered when approaching this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Ziebarth et al had no complications, 2 and at 12 years follow-up they found in 42 patients no AVN and an 9% overall complication rate, though secondary impingement deformi-ties remained in some patients, and secondary surgical procedures undergoing open procedures for impingement deformities (14%). 27 Huber et al 28 found 5 out of 28 patients (18%) with overall complications and 1 (3%) AVN; Madan et al 29 reported 5 out of 28 patients (18%) with overall complications and 4 (14%) AVN, Sankar et al 30 reported 41% with overall complications and 7 out of 27 patients (26%) AVN, and Upasani et al 7 reported 16 out of 43 patients (37%) with overall complications and 10 (23%) AVN. Except the Bernese group, the others had similar complication rates and this is carefully to be considered when approaching this technique.…”
Section: Discussionmentioning
confidence: 99%
“…33 Ziebarth et al recently described a high survival rate at 12 years, probably the longest follow-up available. 27 In this prospect, a longterm analysis is imperative, as the results of MDO must be compared with the natural history of SCFE and with other available techniques. According to medium-/short-term results and overall complication rates, we consider the subcapital osteotomy suitable only for specialized centers, performed by experienced high-volume surgeons and for severe displaced SCFE (!50°).…”
Section: Discussionmentioning
confidence: 99%
“…The epiphysis is then manually reduced on the metaphyseal stump and fixed with anterograde Kirschner wires. 63 Of the hips, 93% presented with no progression of osteoarthritis, good clinical scores and no subsequent total hip arthroplasty (THA) at 10-year follow-up 64 following a modified Dunn procedure. Different rates of avascular necrosis (AVN) are reported for the modified Dunn procedure in the literature with low rates of 4–6% 65 , 66 or high rates of up to 26%.…”
Section: Slipped Capital Femoral Epiphysis (Scfe)mentioning
confidence: 99%
“…Незначительное Показания и противопоказания к модифицированной операции Dunn, которых мы придерживались в своей работе, как и примененная нами техника вмешательства, полностью согласуются с данными литературы [20][21][22]. Между тем в отли чие от большинства авторов [23][24][25][26] у нас отсутствует опыт выполнения этой операции при ЮЭГБК со смещением эпифиза средней степени тяжести. Клинико-рентгенологическая характеристика наших пациентов в рассматриваемые сроки послеоперационного периода, как и количество ранних осложнений хирургического лечения, также соответствуют литературным данным [27][28][29].…”
Section: результаты и их обсуждениеunclassified